The Role of Student’s Language Competence for Producing Negotiation Text - Mega Puspitasari; Andayani Andayani; Sarwiji Suwandi (Indonesian Language and Literature Education Study Program and LPPM State University of Jakarta (Program Studi Pendidikan Bahasa dan Sastra Indonesia dan LPPM Universitas Negeri Jakarta), 2019)
The student’s language competence is a supporting factor that can be used to facilitate communication activities at school or in the community. One of the activities is negotiation. Negotiation needs a language competency for producing negotiating texts, (1) language knowledge including grammer and lexical, (2) strategics competence for finding accurate information on the topic to obtain facts, dare to ask for more than expected, and students must be able to show a firm attitude, and (3) communicative competence including confidence, contextual and effective. Based on these results, the purpose research for describing a Indonesian language competence by students in producing negotiating texts. The research method used is literature study to collect reference data that are relevant to topics from various sources of books, literature and other research results.